2000
DOI: 10.1046/j.1365-2583.2000.00179.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular systematics of the Phlebotomine sandflies of the subgenus Paraphlebotomus (Diptera, Psychodidae, Phlebotomus) based on ITS2 rDNA sequences. Hypotheses of dispersion and speciation

Abstract: Phylogenetic Paraphlebotomus relationships are inferred by a study based on the sequences of ITS2, which has been sequenced in nine Paraphlebotomus species: P. alexandri, P. andrejevi, P. jacusieli, P. kazeruni, P. mireillae, P. mongolensis, P. saevus, P. sergenti and P. similis and in two out-groups species of the subgenus Phlebotomus: P. papatasi and P. duboscqi. Paraphlebotomus alexandri appears as the sister group of all other Paraphlebotomus sandflies. Among the other species, three groupings are clearly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 22 publications
(19 reference statements)
6
50
0
Order By: Relevance
“…As well as permitting the successful and unambiguous typing of most of the sandfly specimens collected in the camps, the present results also allowed for further taxonomic hypotheses. Though not a phylogenetic analysis, the genetic-distance calculations indicated that the subgenus Paraphlebotomus is paraphyletic, confirming the observations made by Depaquit et al (1998Depaquit et al ( , 2000 in an investigation of internal-transcribed-spacer-2 (ITS2) ribosomal DNA. In a taxon-identity tree produced in a recent comparison of ITS2 sequences that included the subgenera Laroussius and Anaphlebotomus, Ph.…”
Section: Discussionsupporting
confidence: 84%
“…As well as permitting the successful and unambiguous typing of most of the sandfly specimens collected in the camps, the present results also allowed for further taxonomic hypotheses. Though not a phylogenetic analysis, the genetic-distance calculations indicated that the subgenus Paraphlebotomus is paraphyletic, confirming the observations made by Depaquit et al (1998Depaquit et al ( , 2000 in an investigation of internal-transcribed-spacer-2 (ITS2) ribosomal DNA. In a taxon-identity tree produced in a recent comparison of ITS2 sequences that included the subgenera Laroussius and Anaphlebotomus, Ph.…”
Section: Discussionsupporting
confidence: 84%
“…A total of 55 papers comparing different species or subspecies within a genus has been recorded (Booth et al, 1991(Booth et al, , 1994Adamson et al, 1993;Maingon et al, 1993;Esseghir et al, 1997;Marcondes et al, 1997;Aransay et al, 2000;Depaquit et al, 2000Depaquit et al, , 2005bDepaquit et al, , 2008aDepaquit et al, ,b, 2014Di Muccio et al, 2000;Esseghir and Ready, 2000;Mukhopadhyay et al, 2000;Soto et al, 2001;Lins et al, 2002;Mazzoni et al, 2002Mazzoni et al, , 2006Mazzoni et al, , 2008Testa et al, 2002;Torgerson et al, 2003;Beati et al, 2004;Pesson et al, 2004;Moin-Vaziri et al, 2007a;Bounamous et al, 2008Bounamous et al, , 2014Perez-Doria et al, 2008a;Absavaran et al, 2009;Kuwahara et al, 2009;Vivero et al, 2009;Azpurua et al, 2010;Franco et al, 2010;Khalid et al, 2010Khalid et al, , 2012Parvizi et al, 2010a,b;Belen et al, 2011;Kruger et al, 2011;Latrofa et al, 2011a,b;Kumar et al, 2012;Randrianambinintsoa et al, 2012Jafari et al, 2013;…”
Section: Resultsmentioning
confidence: 99%
“…The small subunit (SSU, 18S) is used partially or totally (Aransay et al, 2000;Terayama et al, 2008;Azpurua et al, 2010;Ferroglio et al, 2010;Manonmani et al, 2010;Tiwary et al, 2012;Gajapathy et al, 2013;Pech-May et al, 2013), the first internal transcribed spacer (ITS1) has been used one time . The second ITS (ITS2) has been selected 20 times (Depaquit et al, 2000(Depaquit et al, , 2004a(Depaquit et al, ,b, 2008bDi Muccio et al, 2000;Baron et al, 2008;Kuwahara et al, 2009;Florin et al, 2010Florin et al, , 2011Khalid et al, 2010;Belen et al, 2011;Dvorak et al, 2011;Latrofa et al, 2011a,b;Zapata et al, 2012a;Gajapathy et al, 2013;Zhang et al, 2013). Several markers which are parts of the long subunit (LSU, 28S) have been studied four times (Depaquit et al, , 1999Beati et al, 2004;Gajapathy et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the method established in this study would be useful for epidemiological surveillance of leishmaniasis and its vector, Lutzomyia species. Alternatively, additional analyses targeting other genes, such as 12S and 28S rRNA genes, the mitochondrial cytochrome b gene, and internal transcribed spacer 2 (ITS2) regions, promise reliable information [3,6,7,10,[18][19][20]22].…”
Section: Discussionmentioning
confidence: 99%